Ballads and Legends: Media Transformations of Canonical Narratives in Polish and Czech Culture - Jedličková, Alice; Kos, Matěj (Poznańskie Studia Slawistyczne, 2022)
The paper presents a comparative interpretation of recent Czech and Polish transmediations of canonical literary texts and architexts: ballads by K. J. Erben and Polish legends and folk tales, which are generally regarded as representations of both timeless and historical national values. The theoretical framework is built upon the theory of intermediality introduced by W. Wolf and I. O. Rajewsky, the concept of media modalities developed by L. Elleström, and current multimodal research represented by J. Bruhn and others. The transmediations (a film, a crowdfunded comic book, a series of short films employed as online advertisements) are not only subject to analysis of media-specific strategies involved in the artistic transformations; the authors´ motivations, the economic conditions under which the examined media products were made, and the modes of their distribution and participation in cultural communication are taken into account as well. The results of the analysis illuminate the strong influence of the multimedia environment, of the generic frames of individual media and the strategies that authors of the transmediations use to attain success with audiences